Penguatan Kewaspadaan Bencana Hidrologi Daerah Laut dan Pantai dengan Pembelajaran Digital Berbasis Gamifikasi : Studi Kasus SMA Negeri 20 Medan - Reza Taqyuddin; Asima Manurung; Normalina Napitupulu; Yudhistira Adhitya Pratama (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Coastal areas face high risks of hydrological disasters that demand early preparedness, particularly among the youth. However, conventional mitigation education methods often fail to stimulate active student participation. This community service aims to strengthen disaster awareness in coastal and marine environments at SMA Negeri 20 Medan through gamification-based digital learning innovations. The approach was structured experiential learning, comprising digital learning design, socialization of mitigation concepts, and hands-on learning using simulation game media. In these sessions, students were challenged to make tactical mitigation decisions within virtual disaster scenarios. Evaluation of the activity demonstrated significant effectiveness, with student engagement levels recording above 80%. The application of gamification proved to deliver an immersive experience that enabled students to design area mitigation, evidenced by 90% of students successfully achieving the highest scores in the simulation to create disaster-free zones. This activity concludes that integrating gamification into disaster education effectively transforms theoretical understanding into practical competence while enhancing collective student awareness of coastal environmental risks and disaster mitigation.